Sindrom Metabolik sebagai Faktor Risiko Gagal Jantung Kongestif - Erick Hoetama; Bambang Hermawan (The Indonesian Heart Association, 2015)
Background : Congestive heart failure (CHF) and metabolic syndrome (MetS) are both current major cardiovascular problems. Until recently, the connection between them has not been well understood yet. Mets is composed by several facets which is closely related with the pathophysiology of CHF. This study will try to discuss the relationship between Mets and CHF.Methods: We conducted an observational analytic study using cross sectional design. Subjects were gathered from January until March 2015. All data are descriptively presented, and analyzed using bivariate and multivariate method.Results: MetS itself does not account as risk factor for CHF (OR 1,49; CI95% 0,67-3,32; p=0,328). Component of Mets which shows significant relationship with CHF are raised blood pressure (OR 6,82; CI95% 1,47-31,53; p=0,014) and impaired glucose tolerance (OR 5,95; CI95% 3,26-10,85; p=0,000)Conclusion: Some elements of Mets, not Mets per se, are strong independent predictor for congestive heart failure.